A mediation analysis of family members’ knowledge, attitudes, and practices in nutritional and dietary management for gastric cancer patients - Liu, Cailian; Wei, Min; Song, Lijuan (Frontiers in Medicine, 2026)
BackgroundGastric cancer is a leading cause of global cancer mortality, especially in China, with high incidence and death rates. Nutritional status is crucial for prognosis, yet adherence to dietary guidelines remains low. Family caregivers, pivotal in patient care, often lack adequate nutritional knowledge and practices, highlighting the need for targeted interventions to improve outcomes. This study aimed to investigate the knowledge, attitudes, and practices (KAP) of family members regarding nutritional care for gastric cancer patients.MethodsA cross-sectional study was conducted between January and May 2024 at the Department of Medical Oncology, Inner Mongolia Hospital, Peking University Cancer Hospital. Demographic information and KAP scores were collected using structured questionnaires.ResultsAmong 406 valid questionnaires, 216 (53.2%) respondents were female. Median (25, 75%) knowledge, attitude, and practice scores were 27.00 (19.00, 33.00), 31.00 (30.00, 36.00), and 36.00 (34.00, 42.00), respectively. Structural equation modeling revealed that factors like income, nursing support, and training significantly influenced knowledge, attitude, and practice (all p < 0.05). Mediation analyses showed indirect effects of these factors on attitude and practice (all p < 0.05).ConclusionFamily members understand gastric cancer nutritional care and maintain positive attitudes, but their practices are inadequate. Educational interventions are needed to improve caregiver knowledge and implementation.